话语标记 “可是” 在马来西亚华语会话中的语用功能 = Pragmatic functions of discourse marker “Keshi” in conversational Malaysian Mandarin - 胡文绮 Woo, Wen Qi (2016)
“可是” 一词在马来西亚华语会话中的使用频率高。它在传统语言学中属于转折连词，一般被视为表达分句之间的逻辑语义关系、体现分句在语义上所具有的对立性或比较性的衔接手段。在频繁使用的过程中，“可是” 在某些语境中出现语义弱化的现象，有的甚至已经不能反映真值语义；然而这些 “可是” 并不是毫无用途的，它们在会话中仍发挥特定的语用功能。目前，许多基于书面语料的研究往往只关注 “可是” 在真值语义方面的功能；但是当我们观察真实口语语料时，就能发现其中的 “可是” 用法是很难以它的真值语义来解释的。有鉴于此，本研究旨在透过会话分析 (Conversation Analysis) 的视角，籍着真实口语语料，探讨 “可是” 在华语会话中的语用功能。研究结果显示，“可是” 在自然会话中可以出现在话轮首和话轮中的位置。话轮中的 “可是” 主要可作为转折标记，联系前后两个相对比的命题，反映明显或隐含的转折关系。另一方面，出现在话轮首的 “可是” 虽无法反映真值语义，却具备了多种语用功能，即帮助说话者：（一）引入与缓和产生异议的因素；（二）引入新 “话题”；（三）找回旧话题；（四）表达对前述话语的不解与困惑。总的来说，“可是”在口语交际的过程中延伸出了多种语用功能，成为说话者用以引导听话者领受其言外之意的话语标记。“Keshi” has been used frequently in Malaysian Mandarin daily conversations. As a typical advesative conjunction in Mandarin, “keshi” is mainly seen as a cohesive device to express the logical adversative relation and the comparative presented between clauses. In certain contexts of daily conversation, the original sematics of “keshi” weakens, yet this phenomenon simultaneously reveals and displays certain regularities. Previous research have investigated extensively the truth value semantics of “keshi” based on written Mandarin, however, this paper finds that the various uses of “keshi” in natural conversations can hardly be explained with such semantics. Hence, this study aims to investigate the pragmatic functions of “keshi” in real oral discourse through using Conversation Analysis (CA) approach as the analytic framework. As shown by collected data, “keshi” can be used at turn-initial and turn-internal positions in naturally occurring conversations. The main function of “keshi” at turn-internal position is to signal implicit or explicit contrast between two propositions. Although turn-initial position’s “keshi” can barely reflect truth-value semantics, it still performs several pragmatic functions, namely: (1) Prefacing and mitigating indirect disagreement; (2) Introducing a new “topic”; (3) Resuming a previous topic; (4) Expressing confusion towards the previous discourse. In summary, “keshi” has developed several pragmatic functions in daily conversation, thus serving as a discourse marker often used by speakers of Malaysian Mandarin to convey implied meanings.